DAMPAK PANDEMI COVID-19 TERHADAP PERTUMBUHAN EKONOMI DI PULAU JAWA - Anita Widiastuti; Silfiana Silfiana (Jurnal Ekonomi-Qu, 2021)
The Covid-19 pandemic that has hit the world has changed the order of various aspects of life, including Indonesia. Starting from the health, social and economic sectors that were most significantly affected. The economic sector is experiencing recession both at the global and national levels. The island of Java, as the largest contributor in driving the national economic growth rate, cannot be separated from this problem. This study aims to determine how the impact of the Covid-19 pandemic on economic growth in Java Island. This study uses a qualitative descriptive method with a review of various literatures. The results of this study indicate that the economic growth in Java Island which is the most in contraction is Banten Province, namely minus 3.38% and the fastest improving is the Special Region of Yogyakarta Province with the economic growth rate in the fourth quarter of minus 0.68%. To accelerate economic recovery in Indonesia, it must be started from the island of Java because as the largest contributor, namely with the government's policy efforts to revitalize the processing industry, increase access and capital to MSMEs and optimize the use of village funds in alternative development innovations during a labor-intensive pandemic, the development of BUMDes. or developing the potential of a tourist village.